Basic Writing: A Practical Approach - Lorch, Sue. (Boston Little, Brown and Company, 1984)
Basic Writing: A Practical Approach offers practical instruction in writing to students who are beginning their sequence of college writing courses at the basic level. It is premised on the notions that the vast majority of students can learn to write in the forms and the manner that will be expected of them in college and that students best learn to write by writing. it is designed to give students a foundation of writing skills for college by teaching them to develop arguments, support them, and present them to a specific audience. This book also equips students to cope with the major problem areas of beginning writers: vocabulary, spelling, and sentence structure.
Keywords: Writing